The understanding and relevance of knowledge management in educational environment / Adnan Jamaludin and Alwi Mohd Yunus - Jamaludin, Adnan; Mohd Yunus, AIwi (Faculty of Information Management, 2005)
The understanding of knowledge management and its implementation to support the educational institution towards creating knowledge-based society is of vital discussion. This is due to the fact that knowledge is the critical factor, which will determine organization's success in this millennium. Managing knowledge and information will support organization to provide comprehensive know-how to students and academic staffs. The organizational adaptation to leverage knowledge, its resources and experts like teachers and educators are part of the knowledge initiatives. This will help educational institution to deliberately teaching students as preparation towards creating knowledge society and knowledge workers. Knowledge management implementation is a strategy that uses all knowledge-based resources to capture, locate, reuse, codify the existing knowledge and creating new knowledge to support new product and services.